2023
DOI: 10.3390/ijms24119235
|View full text |Cite
|
Sign up to set email alerts
|

The Role of IL-18 in P2RX7-Mediated Antitumor Immunity

Abstract: Cancer is the leading cause of death worldwide despite the variety of treatments that are currently used. This is due to an innate or acquired resistance to therapy that encourages the discovery of novel therapeutic strategies to overcome the resistance. This review will focus on the role of the purinergic receptor P2RX7 in the control of tumor growth, through its ability to modulate antitumor immunity by releasing IL-18. In particular, we describe how the ATP-induced receptor activities (cationic exchange, la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 167 publications
0
6
0
Order By: Relevance
“…Cisplatin is a first-line drug in the treatment of gastric cancer. Concomitantly, P2X7 expression and the derived cytokine IL-18 have been recognized as gastric cancer biomarkers (13,14). Thus, the results suggested that ATP administration may be involved in the modulatory activity of P2X7, which can reverse the GE delay induced by cisplatin.…”
Section: Discussionmentioning
confidence: 94%
“…Cisplatin is a first-line drug in the treatment of gastric cancer. Concomitantly, P2X7 expression and the derived cytokine IL-18 have been recognized as gastric cancer biomarkers (13,14). Thus, the results suggested that ATP administration may be involved in the modulatory activity of P2X7, which can reverse the GE delay induced by cisplatin.…”
Section: Discussionmentioning
confidence: 94%
“…In particular, the ICI responding sample size was too small to allow the Cox model to function, which could explain why we were unable to conclude the prognostic value of free IL-18. In addition, we measured the levels of IL-18-related compounds in the plasma of patients, which could significantly differ from those found in the immediate vicinity of tumors, where immune cells directly interact with tumor cells and can participate in either pro or antitumor responses, as we recently discussed in [ 7 ]. Finally, some of the patients included in our cohort were previously treated with chemo or radiotherapy (see Table 1 ), which could also impact the levels of both IL-18-producing immune cells and IL-18-related compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of IL-18 to tumor progression is controversial. Preclinical studies have shown that IL-18 is required to inhibit tumor growth using either il18 −/− or il18r1 −/− mice, or even by administrating recombinant IL-18 [ 7 ]. In NSCLC patients, IL-18 has been shown to be expressed by tumor cells and to be active, as suggested by its positive correlation with IFN-γ production [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another feature of P2 R X7 is its ability to activate the NLRP3 inflammasome, an event linked to potassium efflux ( Di et al, 2018 ; Muñoz-Planillo et al, 2013 ), which requires both P2 R X7 and TWIK2 activation ( Di et al, 2018 ) and leads to the release of mature IL-1β and IL-18 ( Perregaux et al, 2000 ), through gasdermin D pores. Consequently, P2 R X7 has the ability to trigger an immune response ( Janho Dit Hreich et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%